Karakterisasi Nanokapsul Ekstrak Daun Serunai (Chromolaena odorata L.) dengan Variasi Kitosan-Alginat Menggunakan Metode Emulsi-Difusi: Characterization of Nanocapsules of Serunai Leaf Extract (Chromolaena odorata L.) with Chitosan-Alginate Variations Using the Emulsion-Diffusion Method - Roosma Hatmayana; Noval Noval; Dede Mahdiyah; Rizki Adhie Ramadhani; Nurul Auliyani (Jurnal Surya Medika (JSM), 2022)
Serunai (Chromolaena odorata L.) is a plant that has been widely used in medicine, one of which is as an antidiabetic. But treatment using plant extracts has drawbacks to the solubility of the active substance and its bioavailability in the body. Nanocapsules are one of the systems in particle technology that can solve this problem by utilizing a polymer that will encapsulate the active substance and release it slowly at the intended target. To achieve this, the manufacture of nanocapsules must meet several characteristic requirements such as particle size, potential zeta, absorption efficiency, and emulsion stability. This study was conducted to identify the nanocapsules characteristics of Serunai leaf extract (Chromolaena odorata L.) with chitosan-alginate variations and identify the influence of chitosan-alginate variations on the characteristics of nanocapsules. This study is a laboratory experimental study with a one-group posttest-only design. The manufacture of Serunai leaf extract nanocapsules using the emulsion-diffusion method, which is then characterized including particle size determination, potential zeta determination, absorption efficiency test (%EE), and emulsion stability test. The results obtained from the determination of the particle size of Formula I 196.4 nm, Formula II 264.2 nm, and Formula III 207.4 nm, potential zeta Formula I -36.1 mV, Formula II -40.1 mV, and Formula III -36.5 mV, the formula I %EE values 99.7%, Formula II 99.8%, and Formula III 99.7%, as well as all formulas indicating the emulsion type m/a. Three formulas have met the requirements of nanocapsules characteristics. The formula is best obtained in Formula II with a chitosan concentration of 0.3% and alginate of 0.6%, so chitosan-alginate variations influence the characteristic results.